2023
DOI: 10.1002/hyp.14946
|View full text |Cite
|
Sign up to set email alerts
|

The role of human activities in the weakening of the propagation relationship between meteorological and hydrological droughts in the Heihe River Basin

Abstract: Meteorological droughts could propagate into hydrological droughts and cause agricultural and societal damage. However, the quantitative impact of human activities on the drought propagation has not been well understood. Based on the precipitation and streamflow observational data and hydrological model simulations during 1961-2013, this study analysed the drought propagation characteristics and quantified the impact of human activities on the propagation in the upper and middle reaches of Heihe River Basin. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Drought is divided into three grades by SPI$$ \mathrm{SPI} $$ or SRI$$ \mathrm{SRI} $$ value in this paper, as follows: (a) no drought, with SPI0.25emor0.25emSRI>1$$ \mathrm{SPI}\ \mathrm{or}\ \mathrm{SRI}>-1 $$; (b) moderate droughts, with 1.5<SPI0.25emor0.25emSRI1$$ -1.5<\mathrm{SPI}\ \mathrm{or}\ \mathrm{SRI}\le -1 $$; (c) severe droughts, with SPI0.25emor0.25emSRI1.5$$ \mathrm{SPI}\ \mathrm{or}\ \mathrm{SRI}\le -1.5 $$; The run theory method is used to identify drought events (Wu et al, 2021; Yang et al, 2023). Specifically, SPI00.25emor0.25emSRI0=1$$ {\mathrm{SPI}}_0\ \mathrm{or}\ {\mathrm{SRI}}_0=-1 $$ is defined as the threshold for drought event that is, SPI<SPI00.25emor0.25emSRI<SRI0$$ \mathrm{SPI}<{\mathrm{SPI}}_0\ \mathrm{or}\ \mathrm{SRI}<{\mathrm{SRI}}_0 $$, is recorded as a drought, and the drought severity in duration t$$ t $$ is characterized by ||SPItSPI0$$ \left|{\mathrm{SPI}}_t-{\mathrm{SPI}}_0\right| $$ (or ||SRItSRI0$$ \left|{\mathrm{SRI}}_t-{\mathrm{SRI}}_0\right| $$).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Drought is divided into three grades by SPI$$ \mathrm{SPI} $$ or SRI$$ \mathrm{SRI} $$ value in this paper, as follows: (a) no drought, with SPI0.25emor0.25emSRI>1$$ \mathrm{SPI}\ \mathrm{or}\ \mathrm{SRI}>-1 $$; (b) moderate droughts, with 1.5<SPI0.25emor0.25emSRI1$$ -1.5<\mathrm{SPI}\ \mathrm{or}\ \mathrm{SRI}\le -1 $$; (c) severe droughts, with SPI0.25emor0.25emSRI1.5$$ \mathrm{SPI}\ \mathrm{or}\ \mathrm{SRI}\le -1.5 $$; The run theory method is used to identify drought events (Wu et al, 2021; Yang et al, 2023). Specifically, SPI00.25emor0.25emSRI0=1$$ {\mathrm{SPI}}_0\ \mathrm{or}\ {\mathrm{SRI}}_0=-1 $$ is defined as the threshold for drought event that is, SPI<SPI00.25emor0.25emSRI<SRI0$$ \mathrm{SPI}<{\mathrm{SPI}}_0\ \mathrm{or}\ \mathrm{SRI}<{\mathrm{SRI}}_0 $$, is recorded as a drought, and the drought severity in duration t$$ t $$ is characterized by ||SPItSPI0$$ \left|{\mathrm{SPI}}_t-{\mathrm{SPI}}_0\right| $$ (or ||SRItSRI0$$ \left|{\mathrm{SRI}}_t-{\mathrm{SRI}}_0\right| $$).…”
Section: Methodsmentioning
confidence: 99%
“…Drought is divided into three grades by SPI or SRI value in this paper, as follows: (a) no drought, with SPI or SRI > À 1; (b) moderate droughts, with À1:5 < SPI or SRI ≤ À 1; (c) severe droughts, with SPI or SRI ≤ À 1:5; The run theory method is used to identify drought events (Wu et al, 2021;Yang et al, 2023). Specifically, SPI 0 or SRI 0 ¼ À1 is defined as the threshold for drought event that is, SPI < SPI 0 or SRI < SRI 0 , is recorded as a drought, and the drought severity in duration t is characterized by SPI t À SPI 0 j j(or SRI t À SRI 0 j j ).…”
Section: Spi and Srimentioning
confidence: 99%
See 2 more Smart Citations
“…To date, numerous studies have investigated the drought propagation characteristics at watershed, national and global scales (Huang et al., 2017; Q. Li et al., 2022; Ma et al., 2019, 2023; Shi et al., 2022; Xu et al., 2019; Yang et al., 2023; Zhou et al., 2021). Van Loon (2015) stated that the onsets of agricultural and hydrological droughts were usually later than that of meteorological drought, and concluded that the drought propagation could be characterized by pooling, lagging, attenuation and lengthening.…”
Section: Introductionmentioning
confidence: 99%